(untitled) - Pan, Wen'guo. (London, 2007)
Contrastive Linguistics is the first book written by a linguist from mainland China on the histories and principles of comparing and contrasting Chinese and Western languages, specifically English. From Wilhelm von Humboldt's initial study in comparative linguistics to the present day, traditional scholarship in contrastive linguistics has taken a Western perspective and shown how foreign languages relate to the Indo-European language family. However, such a view has a limited scope, and there is an alternative history to contrastive linguistics.
Keywords: Ngôn ngữ học,Second language acquisition,Ngôn ngữ thứ hai,Linguistics